HAK ASASI MANUSIA DAN TANTANGAN EKSPLOITASI SUMBER DAYA ANTARIKSA - Johan Rosihan (Lembaga Penelitian dan Pengabdian kepada Masyarakat STIH Awang Long, 2026)
Advances in space technology have brought humanity to the brink of commercializing space resources, including mining on the Moon and asteroids. These activities trigger fundamental legal debates regarding wealth distribution and the protection of human rights. This research analyzes the risks of space resource monopolies by developed nations and private corporations, which potentially infringe upon human rights—specifically the right to development and the right to the common heritage of mankind. The research problems addressed include: (1) how the international legal framework balances the commercial rights of investors with the principle of human rights protection for all humanity in space exploitation, and (2) the positions and challenges of ASEAN countries in facing the international space exploitation regulatory race. The research method employed is normative juridical with a conceptual approach through the